Multi-channel approaches for musical audio content analysis - João Carlos Couto Antunes Fonseca (2020)
The goal of this research project is to undertake a critical evaluation of signal representations for musical audio content analysis. In particular it will contrast three different means for undertaking the analysis of micro-rhythmic content in Afro-Latin American music, namely through the use of: i) stereo or mono mixed recordings; ii) separated sources obtained via state of the art musical audio source separation techniques; and iii) the use of perfectly separated multi-track stems. In total the project comprises the following four objectives: i) To compile a dataset of mixed and multi-channel recordings of the Brazilian Maracatu musicians; ii) To conceive methods for rhythmical micro-variations analysis and pattern recognition; iii) To explore diverse music source separation approaches that preserve micro-rhythmic content; iv) To evaluate the performance of several automatic onset estimation approaches; and v) To compare the rhythmic analysis obtained from the original multi-channel sources versus the separated ones to evaluate separation quality regarding microtiming identification.